Evaluasi Kualitas Website Menggunakan Webqual 4.0 (Studi Kasus: Sistem Informasi Kebencanaan Kabupaten Boyolali) - Ramadhan, Muhammad Rizky; Hartomo, Kristoko Dwi (Jurusan Teknologi Informasi Universitas Semarang, 2022)
This study aimed to measure the quality of the Disaster Mitigation Information System (Sikabi) belonging to the Regional Disaster Management Authority of Boyolali Regency. Quality tests are carried out to determine the quality and functionality of the system that functions optimally and can display accurate, easily accessible, and useful information for disaster mitigation in the region. The results of the study are useful for providing feedback to information system developers regarding the quality of the website usability aspect, the quality of the information presented, and the quality of the interactions provided as well as the user satisfaction at accessing the Disaster Information System website. This study uses the Webqual 4.0 method which has 4 assessment variables, namely in terms of usability (information quality), interaction service (interaction quality), and user satisfaction while accessing the website (overall impression). From the research results, the information quality variable has a sig value. 0,000 <0,05 which indicates that there is an influence of information quality on user satisfaction in using the Sikabi website. Therefore, we recommend improving the quality of the information displayed on the Sikabi website page.